Технологічне забезпечення якості підкладок функціональних компонентів мікрооптоелектромеханічних систем - Чала, О. О. (ХНУРЕ, 2021)
Дисертаційна робота присвячена вирішенню актуальної науково-прикладної задачі підвищення якості ФК (функціональних компонентів) МОЕМС (мікроелектромеханічних систем) за рахунок технологічного забезпечення, розробки та удосконалення методів прогнозування й оцінки характеристик підкладок ФК МОЕМС. Розроблено моделі та метод забезпечення якості підкладок ФК МОЕМС, які дозволяють прогнозувати стан підкладок ФК під впливом технологічних факторів під час їх виготовлення. Розроблено модель впливу параметрів технологічних операцій шліфування та полірування на параметри формоутворення ФК MOEMС, що дозволяє визначити величину вихідних параметрів для отримання заданих чисельних значень шорсткості. Розроблено технологічний процес контролю підкладок ФК МОЕМС, що направлений на підвищення точності та відтворюваності інформації, зниження трудомісткості. Створено експериментальний макет і проведено дослідження запропонованих методів. У результаті проведених експериментальних досліджень отримано дані, які дали змогу дати оцінку вплив параметрів ФК МОЕМС-перемикачів на розсіювання оптичної потужності. Отримано результати, відповідно до яких можна провести побудову й аналіз залежностей вихідних параметрів підкладок ФК МОЕМС на розсіювання оптичної потужності. На основі проведених досліджень розроблено технологічний процес виготовлення підкладок ФК МОЕМС. Electronics, Kharkiv, 2021. The dissertation work is dedicated to the actual scientific and applied task of improving the quality of FC (functional components) MOEMS (microoptoelectromechanical systems) through technological support, development and improvement of methods for predicting and evaluating the characteristics of FC MOEMS substrates. Models and a method for ensuring the quality of MOEMS FC substrates have been developed, which make it possible to predict the state of PC substrates under the influence of technological factors during their manufacture. For the first time, a physicaltechnological model for predicting substrate defects of functional components of microoptoelectromechanical systems has been proposed, which takes into account the quality of the substrate layer and makes it possible to predict the parameters of technological processes that can lead to the appearance of technological defects in substrates, as well as to correct the technological processes of their manufacture. A model of the influence of the parameters of technological operations of grinding and polishing on the parameters of the formation of FC MOEMS has been developed, which makes it possible to determine the value of the parameters for obtaining the specified numerical values of the roughness. A technological process for controlling MOEMS FC substrates has been developed and investigated, aimed at increasing the accuracy and reproducibility of information, and reducing labor intensity. The method takes into account the relationship between the thickness of the layer for removing defects in the functional components of microoptoelectromechanical systems and the factors of shaping: speed, time and granularity of the polishing paste and their combined effect. This makes it possible to determine the parameters of the surfaces of the functional components of micro-optoelectromechanical systems. It is proposed to use the interference method in the technological quality control of functional micro-optoelectromechanical systems. This is realized by eliminating the accompanying components in the images using the proposed adaptive filter. This makes it possible to increase the reliability of the reproduction of the parameters of shaping of the functional components of micro-optoelectromechanical systems and to expand the functionality of the control technology methods. A method for identifying the extrema of interference fringes of images in the technological process of monitoring the surfaces of functional components of micro-optoelectromechanical systems is proposed, which differs in the determination of the phase function from the ratio of the useful and complexly coupled with Hilbert signal components, which makes it possible to increase the reliability of determining the parameters. An experimental model was created and the proposed methods were studied. As a result of the experimental studies, data have been obtained according to which it is possible to construct and analyze the dependences of the parameters of the MOEMS FC substrates on the scattering of optical power. It was determined that to obtain the value of the coefficient of reflectance for scattering less than 10%, the surface roughness of the FC should be less than 57 nm, while the scattering ability is almost independent of the wavelength of the beam within the investigated wavelength region, but depends on the quality of the substrate of the MOEMS FC. The results are obtained, in accordance with which it is possible to construct and analyze the dependences of the parameters of the MOEMS FC substrates on the scattering of optical power. On the basis of the studies carried out, a technological process for the fabrication of MOEMS FC substrates has been developed.
Keywords: мікрооптоелектромеханічні системи; функціональний компонент; підкладка; фізико-технологічна модель; модель прогнозування, формоутворення; неруйнівний контроль; технологічний процес; microoptoelectromechanical systems; functional component; surfaces; physical-technological model; forecasting model; formation; non-destructive testing; technological process